Co-Production of Prolonged, Complex, and Negative Services: An Examination of Medication Adherence in Chronically Ill Individuals. (August 2015) - Spanjol, Jelena; Cui, Anna S.; Nakata, Cheryl; Sharp, Lisa K.; Crawford, Stephanie Y.; Xiao, Yazhen; Watson-Manheim, Mary Beth
This study examines customer coproduction in a prolonged, complex, and negative service context—medication adherence in chronically ill individuals. We integrate services and medical perspectives to develop a novel theoretical framework of adherence as a nested system of coproduction behaviors, characterized by temporal and scope dimensions. Utilizing a qualitative approach, our findings point to two key insights about coproduction in the customer sphere. First, the enactment and form of regular-restricted, intermittent-intermediate, and irregular-expansive coproduction behaviors are determined by the characteristics of the customer sphere—that is, coproduction is contextualized . Second, the coproduction system in the customer sphere is complex and the different levels are interdependent . Our research contributes to the emerging literature on service coproduction by elucidating the behaviors through which customers strive toward adherence. The identified coproduction framework holds important implications for providers of prolonged and complex services and future research directions.